ECG DISPERSION MAPPING PARAMETERS DURING THE TREADMILL TEST IN PATIENTS WITH CORONARY HEART DISEASE - G. G. Ivanov; E. V. Agafoshina; A. A. Pecherskikh; G. Khalabi (Кардиоваскулярная терапия и профилактика, 2013)
Aim. The aim of the study was the complex analysis of the ECG-12 and ECG dispersion mapping (DM) parameters during the physical stress test in patients with coronary heart disease (CHD).Material and methods. The main group included 143 CHD patients with Functional Class I–III angina (99 men and 44 women; mean age 50,6±4,6 years). The control group included 37 healthy individuals (mean age 44,3±4,8 years). Patients with heart failure signs and symptoms were excluded. All participants underwent the graduated physical stress test.Results. Two variants of the ECG changes were observed, with normal and abnormal reaction of ECG DM parameters. The latter group was characterised by the following: ratio of heart rate and myocardial micro-alternation index (HRmax/MMImax) 30% at the peak HR.Conclusion. Using the ECG DM method during the treadmill test is a feasible and useful approach to gain additional diagnostic information on the myocardial electro-physiological status and, therefore, to select the patients who need further examination and treatment.